Interpersonal emotion regulation in young adults with low and high psychosis proneness: a diary study - Riehle, Marcel; Brauer, Saskia; Lincoln, Tania; Prüßner, Luise (PsyArXiv preprints, 2023)
Emotion regulation is a complex process that often involves the presence of others, also known as interpersonal emotion regulation (IER). Nevertheless, studies on emotion regulation difficulties in psychosis and psychosis risk states have neglected IER. This study investigated whether young adults with elevated psychosis proneness engage in IER less frequently and find it less helpful than those with low psychosis proneness. Psychosis-prone participants with attenuated negative (PP-NES, n=37) and positive symptoms (PP-POS, n=20) and low psychosis-prone participants (control group, CG, n=52) were recruited based on a priori defined cut-offs for the Community Assessment of Psychic Experiences. Participants provided daily diaries over one week, reporting negative symptoms, paranoia, positive and negative affect, and the frequency and efficacy of IER strategies to upregulate positive and downregulate negative emotions. Multilevel models showed that PP-NES reported using IER to upregulate positive emotions less frequently and found it less effective for both positive and negative emotions compared to CG. PP-POS did not differ from CG on any IER measure. Additionally, negative symptoms were negatively associated with all IER measures on the same day, and paranoia was associated with more frequent use of IER to downregulate negative emotions. These findings suggest deficits in everyday interpersonal emotion regulation in psychosis-prone young adults with negative symptoms. Moreover, the results indicate that young adults use interpersonal emotion regulation more when in paranoid states. Future research should investigate the consequences of these aberrations regarding social inclusion and short- and long-term symptom trajectories.
Gesehen am 13.06.2024